Dentatin isolated from Clausena excavata induces apoptosis in MCF-7 cells through the intrinsic pathway with involvement of NF-kB signalling and G0/G1 cell cycle arrest: A bioassay-guided approach - Arbab, I.A.; Abdul, A.B.; Sukari, M.A.; Abdullah, R.; Syam, S.; Kamalidehghan, B.; Ibrahim, M.Y.; Taha, M.M.E.; Abdelwahab, S.I.; Ali, H.M.; Mohan, S. (Elsevier, 2013)
Ethnopharmacological relevance: Clausena excavata Burm. f. has been used in folk medicines in eastern Thailand for the treatment of cancer. Materials and methods: To investigate the apoptosis mechanism, we isolated dentatin (DTN) from this plant using a bioassay-guided approach. DTN-induced cytotoxicity was observed with the MTT assay. Acridine orange/propidium iodide staining was used to detect cells in early apoptosis and high content screening (HCS) to observe nuclear condensation, cell permeability, mitochondrial membrane potential (MMP) and cytochrome c release. Apoptosis was confirmed with a clonogenic assay, DNA laddering and caspase 3/7 and 9 assays. Reactive oxygen species (ROS) formation, Bcl-2 and Bax expression, and cell cycle arrestwere also investigated. The involvement of nuclear factor-kappa B (NF-kB) was analysed with the HCS assay. Results: A significant increase in chromatin condensation in the cell nucleus was observed by fluorescence analysis. Apoptosis was confirmed by the reduced number of colonies in the clonogenic assay and the increased number of cellular DNA breaks in treated cells observed as a DNA ladder. Treatment of MCF-7 cells with DTN encouraged apoptosis with cell death-transducing signals that reduced MMP by down-regulation of Bcl-2 and up-regulation of Bax, triggering cytochrome c release from the mitochondria to the cytosol. The released cytochrome c triggered the activation of caspase 9 followed by the executioner caspase 3/7. DTN treatment significantly arrested MCF-7 cells at the G0/G1 phase (po0.05) and ROS was significantly elevated.Moreover, DTN significantly blocked the induced translocation of NF-kB fromcytoplasmto nucleus. Conclusion: Together, the results demonstrated that the DTN isolated from Clausena excavata inhibited the proliferation of MCF-7 cells, leading to cell cycle arrest and programmed cell death, which was confirmed to occur through the mitochondrial pathway with involvement of the NF-kB signalling pathway.